2015
DOI: 10.1146/annurev-pharmtox-011112-140226
|View full text |Cite
|
Sign up to set email alerts
|

Eph Receptors and Ephrins: Therapeutic Opportunities

Abstract: The Eph receptor tyrosine kinase family plays important roles in developmental processes, adult tissue homeostasis and various diseases. Interaction with ephrin ligands on the surface of neighboring cells triggers Eph receptor kinase-dependent signaling. The ephrins can also transmit signals, leading to bidirectional cell contact-dependent communication. Moreover, Eph receptors and ephrins can function independently of each other, through interplay with other signaling systems. Given their involvement in many … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
297
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 260 publications
(301 citation statements)
references
References 169 publications
(330 reference statements)
4
297
0
Order By: Relevance
“…Interestingly, TCGA data analysis revealed that EphA2 and EfnA1 alterations occur independently, and it is intriguing to hypothesize that tumors with EphA2 and EfnA1 coexpression might be negatively selected in the early stages of tumor development. However, the overexpressed EphA2, in the absence of cognate ligands (23,24,30,41), can function to promote tumorigenesis in a ligand-independent manner. Overexpressed EPHA2 can be phosphorylated at S897 by activated AKT and can function in a ligand-independent manner to promote cell growth, xenograft tumor development, anoikos resistance (42), and migration of tumor cells (43)(44)(45)(46).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, TCGA data analysis revealed that EphA2 and EfnA1 alterations occur independently, and it is intriguing to hypothesize that tumors with EphA2 and EfnA1 coexpression might be negatively selected in the early stages of tumor development. However, the overexpressed EphA2, in the absence of cognate ligands (23,24,30,41), can function to promote tumorigenesis in a ligand-independent manner. Overexpressed EPHA2 can be phosphorylated at S897 by activated AKT and can function in a ligand-independent manner to promote cell growth, xenograft tumor development, anoikos resistance (42), and migration of tumor cells (43)(44)(45)(46).…”
Section: Discussionmentioning
confidence: 99%
“…Binding of Ephrin A1 (EFNA1) to EPHA2 results in phosphorylation of EPHA2 and activation of a downstream signaling cascade that regulates various cellular processes, including cell shape, movement, angiogenesis, survival, and proliferation (23,24). In cancer, EphA2 has been reported to be both tumor-promoting and tumor-inhibiting although a large amount of evidence points to its tumor suppressor activity (23,24). EphA2 knockout mice were shown to be very susceptible to DMBA/ TPA-induced skin carcinogenesis (25).…”
mentioning
confidence: 99%
“…1−3 However, increased EphA4 expression and aberrant kinase activity following nervous system injury or disease can contribute to pathological processes. 1,3 EphA4 was identified as a gene promoting disease pathogenesis in amyotrophic lateral sclerosis (ALS), and studies in ALS animal models and patients have shown that reduced EphA4 activity delays disease onset and slows disease progression. 4 Evidence in cultured neurons and mouse models has also implicated EphA4 activity in the synaptic dysfunction induced by the pathogenic amyloid-β oligomers in Alzheimer's disease.…”
mentioning
confidence: 99%
“…1−3 The two main strategies that could be used to inhibit the detrimental effects of EphA4 activity involve blocking either its kinase activity or its interaction with ephrin ligands. 1,2 To our knowledge, high affinity, selective EphA4 kinase inhibitors remain to be identified. 1,3 In contrast, selective and high affinity peptide antagonists targeting the ephrin-binding pocket in the extracellular ligand-binding domain (LBD) of EphA4 are available.…”
mentioning
confidence: 99%
See 1 more Smart Citation